Efetividade na adesão a reabilitação auditiva em crianças: Grupo de Adesão Familiar e terapia inicial - Youssef, Bruna Capalbo (2017)
Introduction: Early diagnosis of hearing loss in children, in the first months of life, with intervention, can be considered as determining factors for the development of hearing and language skills. Factors such as: The effective use of the electronic device; The quality of amplification; Family expectations and their implication with treatment are important factors for the child's prognosis, as well as aspects related to socioeconomic, cultural and academic conditions. Objective: The objective of this study was to verify the process of adherence to auditory rehabilitation, in addition to describing and contextualizing barriers and facilitating factors involved in adherence in the initial stages of the rehabilitation process (ADAPTI), including consistency of use of hearing aids, In the therapies and in the group activities in the initial phase of the therapeutic process of children with hearing impairment in the first years of life, in a service of the Municipal Health of São Paulo. Method: The study was realizated with children with hearing loss attended at the Center for Hearing in Children (CeAC), their parents and therapists, in the initial stage of adaptation of the electronic device and initial therapy - ADAPTI. This study has descriptive quanti/qualitative character. The patients were characterized from the demographic, audiological, socioeducational point of view, auditory development, distance and transportation from the residence to the service, the consistency of hearing aids use and the effectiveness of the process in the adhesion to auditory rehabilitation. Results: The 25 children were organized into five groups. Of these, 13 were female and 12 male. 24 patients had sensorineural hearing loss and used digital retroauricular hearing aids. One child had conductive loss and used AASI adapted with a bone vibrator. Ten had suspicion or presence of other compromises. Four started at LIBRAS school during the ADAPTI period. We classify the subjects according to the outcome of their ADAPTI process and referral to the network for therapy and/or school, an outcome that we call effectiveness of the process of adherence to auditory rehabilitation. We used three classes, respectively: 1 - understanding/adherence to the auditory rehabilitation process, 2 - partial understanding/adherence to the auditory rehabilitation process, and 3 – non understanding/adherence to the auditory rehabilitation process. The composition of the groups was quite heterogeneous. In several dynamics we could observe that the different prognoses, depending on the characteristics of each pacient interfered in the orientations, often generating a disinterest of the parents with different demands. The distance between the residence and the service and audibility with AASI showed significant differences when comparing the 3 groups. Difficulties in using the hearing aids in the ear due to problems with the mold and other compromises seem to affect the consistency of use of the hearing aid; The same did not happen with daycare/school. Of the 25 subjects, 19 obtained a vacancy of speech therapy near their residence, the time to obtain the vacancy ranged from 0 to 15 weeks. Discussion: The group was considered by the parents as a facilitator in the process of adherence in auditory rehabilitation. In addition, more homogeneous groups seemed to lead to greater empathy among the participants, sharing difficulties and achievements, facilitating group dynamics and, consequently, greater likelihood of adherence. The distance and SII 65 dB are factors that seem to affect adherence to the process of auditory rehabilitation. The consistency of using the hearing aids seems to be a multifactorial variable that does not necessarily represent a non adherence to the auditory rehabilitation process, it can be affected when we relate problems with the molds and other comprometments. Regarding the counter-referral process, all cases were referred to their home region before the ADAPTI process was finalized, which was effective in 75% of the cases. Conclusion: We conclude from the results and the discussion of the study that the formation of GrAF more homogeneous, carried a greater probability of effective adhesion; The activities proposed in the GrAF led to discussions that promote a facilitator of adherence to treatment; The GrAF was considered by parents and guardians who participated as a facilitator in this process; The distance from the residence to the service and the variation of SII 65 dB were factors that represented a barrier in adhesion; The consistency of the use the hearing aids appeared to be a multifactor variable that does not necessarily represent non compliance; Difficulties in maintaining hearing aids in the subjects ears, especially with regard to problems with the mold and other comprometments associated with hearing loss, seemed to interfere in the consistency of hearing aids use; There are still barriers as to the effectiveness and efficiency of the counter referral process